Pengembangan media pembelajaran PPKn kelas XI menggunakan Articulate Storyline di Madrasah Aliyah Muhammadiyah Tanjuang Bonai - septianti, ira; Usmanto, Heri (Civic Education Perspective Journal, 2024)
The purpose of this study was to produce an android-based PPKn learning media with the help of Articulate Storyline software which was tested on class X1 students of Madrasah Aliyah Muhammadiyah Tanjuang Bonai. This development research was conducted using the ADDIE development model which includes Analysis, Design, Development, Implementation, and Evaluation. Validation was carried out by media experts with a percentage of 85% "very good category", material experts obtained a score with a percentage of 82% included in the "Good" category, language experts obtained a score with a percentage of 91.1% with the category "very decent", and the assessment of subject teacher responses by obtaining a percentage of 92.7% categorized as "Very Good" and the media developed was tested on class XI students of Madrasah Aliyah Muhammadiyah Tanjuang Bonai. Based on the results of the research and discussion, it can be concluded that the android-based learning media using Articulate Storyline in the PPKn subject for class XI is very good and feasible to be used by teachers and students as a learning media in the PPKn subject for class XI at Madrasah Aliyah Muhammadiyah Tanjuang Bonai.